Mythology as history - Rossington, M; Rossington, Michael (1988)
﻿ This thesis examines Shelley's interest in the mythologies of non-Christian cultures. It argues that Shelley's use of mythology can be best understood as an artistic response to his perception of contemporary historical events and within the context of the hostility of the younger Romantic poets towards the religious and political beliefs of the elder generation. The theological defence of the Mosaic account of the origins of the world by orthodox Christians set against the sympathy towards pagan culture expressed by secular historians and antiquarians of the late eighteenth and early nineteenth-centuries forms a recurrent theme in the background to Shelley's interest in myth. While criticism has often seen Romanticism itself as a mythological tendency in defiance of Enlightenment scepticism, the starting-point for Shelley's examination of the origins of religious belief, witnessed in "Mont Blanc", is his refutation of Christian monotheism and his preference for an explanation of the basis of religion and mythology in the primitive fear of Nature. Combined with his Enlightenment optimism in historical progress, the use of Zoroastrianism encourages the invention of his own myths of origins and of historical destiny in Prometheus Unbound and "The Witch of Atlas", which overcome the regressive doctrine of original sin and defy the historical actuality of the failure of the French Revolution. The presence of the Orient in Shelley's mythological poetry can be interpreted in terms of a critique of "Romantic Hellenism", a category which has failed to account for his sympathy with the popular natural religion of Bacchus, a figure associated in classical history with the East, who represents the antithesis of the rational, Hellenic Apollo. In the final two years of his life, Shelley develops a different kind of mythologised history in which an idealist defence of the poet is incorporated into the Enlightenment concept of philosophical history. It is this investment which he questions in "The Triumph of Life".